The Influence of Psychological Climate, Work-Life Balance, and Organizational Culture on the Performance of Account Representative (AR) Employees at KPP Madya Surabaya - Kurniawati, Dyah Ayu; Rahayu, Sri; Sundjoto, Sundjoto; Fitrianty, Rifda (Transpublika Publisher, 2026)
A key challenge in enhancing organizational effectiveness lies in identifying the factors that most significantly drive employee performance within specific institutional contexts. The objective of this research is to analyze the effects of Psychological Climate, Work Life Balance, and Organizational Culture on the performance of Account Representatives at KPP Madya Surabaya. A quantitative methodology with an associative design is utilized to achieve this aim. The population consisted of 40 Account Representatives, all of whom were included as the research sample using a census method. Employing a Likert-scale questionnaire and multiple linear regression analysis, this study found that Psychological Climate, Work Life Balance, and Organizational Culture have both significant partial and simultaneous effects on employee performance. These findings indicate that positive perceptions of the work environment, balanced personal and professional life, and strong organizational cultural values contribute to improved employee performance. The coefficient of determination further demonstrates that most of the variation in employee performance can be explained by these three variables. This study concludes that strengthening Psychological Climate, Work Life Balance, and Organizational Culture is an essential strategy for enhancing the performance of Account Representatives at KPP Madya Surabaya.